Equilibrium Vertical Foreclosure: Reply - Ordover, Janusz A.; Saloner, Garth; Salop, Steven C. (American Economic Review, 1992)
In Ordover, Saloner, and Salop (1990; hereafter OSS) we showed that a downstream duopolist may have an incentive to backward integrate in order to foreclose its downstream rival from a source of upstream supply. As a result of the vertical integration, the downstream rival's input price increases, giving the integrating firm a competitive advantage in the downstream market. Moreover, in equilibrium, the foreclosed downstream rival does not find it profitable to negate these effects by integrating itself. OSS considers a four-stage game involving two upstream firms, Ul and U2, and two downstream firms, Dl and D2. In the first stage, the downstream firms can bid to acquire Ul. If there is an acquisition, (say, Dl acquires Ul to form F1), upstream input prices are set in the second stage. In the third stage, knowing the input prices it faces, D2 can attempt to acquire U2. Finally, in the fourth stage, Dl and D2 compete 'a la Bertrand with differentiated products. In his comment, David Reiffen (1992) makes three distinct points. First, he notes that once Dl has acquired Ul, the equilibrium of the subsequent subgame depends critically on how upstream prices are set in the second stage. He argues that our results depend on the ability of Fl to commit to a high upstream price. This criticism previously has been made by Oliver Hart and Jean Tirole (1990). We show below that the results in OSS do not depend on the ability of Fl to commit. Instead, our main result stems from the fact that vertical integration changes the firm's incentives to engage in price-cutting in the input market. The notion that vertically integrated firms behave differently from unintegrated ones in supplying inputs to downstream rivals would strike a businessperson, if not an economist, as common sense.1 We show that there is theoretical merit to that common-sense view. Second, Reiffen argues that the game considered by OSS is similar to a game in which there is no vertical integration but, rather, where a nonintegrated Dl has a first-mover advantage in the downstream market. In such a game, Dl benefits from the ability to commit to the price that its Stackelberg leadership position gives it. Reiffen considers this to be additional evidence in support of the claim that OSS depends critically on Fl's ability to commit, not on vertical integration. We explain why the mechanism by which Dl is able to raise its profits in the sequential one-shot game considered by Reiffen is conceptually quite different from the mechanism by which Dl profits from vertical integration in OSS. Third, Reiffen argues that our results depend on there being only two upstream firms. This is correct in the symmetric Bertrand model analyzed. However, as we discuss below, our results do obtain as long as the upstream price is decreasing in the number of firms, as occurs in many oligopoly models, particularly when costs vary across firms. The next section summarizes the conceptual problems pertaining to upstream pricing. These problems are resolved in Section II by means of simple and natural price * Ordover: Department of Economics, New York University, 269 Mercer St., 7th Floor, New York, NY 10003; Saloner: Graduate School of Business, Stanford University, Stanford, CA 94305; Salop: Georgetown University Law Center, 600 New Jersey Avenue NW, Washington, DC 20001. We have benefited greatly from several discussions with Faruk Gul. Research support from the National Science Foundation (grant 8813943-IRI), the Sloan Foundation, and the C. V. Starr Center for Applied Economics at NYU is gratefully acknowledged. 'For example, the Japan-U.S. Strategic Impediments Initiative is predicated on the proposition that the loosely linked Japanese firms that form the various keiretsu do discriminate against nonaffiliated firms.